Mercury distribution and transfer in mangrove forests in urban areas under simulated rising sea levels - You, Xilin; Sun, Lumin; Chen, Xiaozheng; Li, Yiting; Zheng, Jue; Yuan, Dongxing; Wu, Junjie; Sun, Shiyu (Frontiers in Marine Science, 2024)
In this study, the impact of simulated sea level rise (SLR) on the distribution and migration of mercury in an urban mangrove wetland was assessed. Located on the northern coast of Maluan Bay in Xiamen City, Fujian Province, China, the study area comprises two adjacent Kandelia obovata mangrove plots with elevations representative of a 40-cm SLR and the current sea level, respectively. By examining the differences in total mercury (THg), methylmercury (MeHg), and mercury isotopes in sediments from different elevations, we reveal the geochemical behavior of THg and MeHg under a simulated 100-year SLR scenario. Our results indicate that the distribution of THg and MeHg in sediments mirrors the distribution patterns of biogenic elements such as carbon, nitrogen, and phosphorus, suggesting that THg and MeHg mainly enters the sediment through the adsorption onto enrichment of organic matter. Notably, the concentrations of THg and MeHg, total organic carbon (TOC), total nitrogen (TN), and total phosphorus (TP) in low-elevation plots were significantly higher than those in high-elevation ones, implying that SLR enhances the retention capacity of mangrove wetlands for THg, MeHg and nutrients. Mercury isotope characteristics reveal that the primary mercury source in the study area is anthropogenic emissions from surrounding lands, entering the wetland from both landward and seaward. This study highlights the crucial role of mangrove wetlands in mercury pollution control and nutrient cycling in the context of SLR, providing a scientific basis for mangrove conservation and restoration. Furthermore, the results offer a new perspective on the geochemical behavior of mercury in vegetated intertidal ecosystems against the background of a warming climate.